2018
DOI: 10.1039/c7ob03164e
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the properties of a hypoxia-responsive 1,8-naphthalimide for imaging applications

Abstract: Sensing hypoxia in tissues and cell models can provide insights into its role in disease states and cell development. Fluorescence imaging is a minimally-invasive method of visualising hypoxia in many biological systems. Here we present a series of improved bioreductive fluorescent sensors based on a nitro-naphthalimide structure, in which selectivity, photophysical properties, toxicity and cellular uptake are tuned through structural modifications. This new range of compounds provides improved probes for imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
2
19
0
2
Order By: Relevance
“…As is the case with DMSC primary cells, DMSC23 cells are resistant to oxidative stress due to the preconditioning of the placenta‐derived tissue where the cells are isolated from . We previously showed that DMSC23 are more resistant to hypoxic stress compared to CMSC29 . Since EVs convey similar properties to the cells which they are secreted from, DMSC23 EVs were expected to reduce oxidative stress in an established in vitro model of lung injury; LPS‐injured BEAS‐2B lung epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…As is the case with DMSC primary cells, DMSC23 cells are resistant to oxidative stress due to the preconditioning of the placenta‐derived tissue where the cells are isolated from . We previously showed that DMSC23 are more resistant to hypoxic stress compared to CMSC29 . Since EVs convey similar properties to the cells which they are secreted from, DMSC23 EVs were expected to reduce oxidative stress in an established in vitro model of lung injury; LPS‐injured BEAS‐2B lung epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the naphthalimides with substituents at the C3 and C5 position have either been previously reported, or were readily accessible by adaptation of previous methods (Scheme S1). Substitution at the C6 position, however, is rarely reported in the literature and was less straightforward for many of the substituents.…”
Section: Resultsmentioning
confidence: 99%
“…We envisaged that the incorporation of nitro‐aryl substituents onto the 4‐amino‐1,8‐naphthalimide scaffold would provide a suitable model system in which to examine the above properties, anticipating that the resulting molecules would be useful probes for sensing hypoxic environments, since aromatic nitro compounds are known to be reduced to the corresponding aniline in hypoxic conditions . Nitro groups generally quench fluorescence, whereas in amine‐containing fluorophores, strong fluorescence is common.…”
Section: Introductionmentioning
confidence: 99%